DNA bipedal motor walking dynamics: an experimental and theoretical study of the dependency on step size. - Khara, D; Schreck, J; Tomov, T; Berger, Y; Ouldridge, T; Doye, J; Nir, E (Oxford University Press, 2017)
We present a detailed coarse-grained computer simulation and singlemolecule fluorescence study of the walking dynamics and mechanism of a DNA bipedal motor striding on a DNA origami. In particular, we study the dependency of the walking efficiency and stepping kinetics on step size. The simulations accurately capture and explain three different experimental observations. These include a description of the maximum possible step size, a decrease in the walking efficiency over short distances and a dependency of the efficiency on the walking direction with respect to the origami track. The former two observations were not expected and are non-trivial. Based on this study, we suggest three design modifications to improve future DNA walkers. Our study demonstrates the ability of the oxDNA model to resolve the dynamics of complex DNA machines, and its usefulness as an engineering tool for the design of DNA machines that operate in the three spatial dimensions.